2019
DOI: 10.1021/acsaem.8b01820
|View full text |Cite
|
Sign up to set email alerts
|

Durable High Polymer Content m/p-Polybenzimidazole Membranes for Extended Lifetime Electrochemical Devices

Abstract: A series of high polymer content phosphoric acid-doped m/p-polybenzimidazole (PBI) copolymer membranes were prepared via the poly­(phosphoric acid) (PPA) process. These copolymer membranes showed much higher solubility in solution (7–10 wt %) compared to the homopolymer para-PBI (typically <3.5 wt %), which translated to higher polymer solids content in the PPA-processed doped membranes. Concurrent with these changes, the compressive creep compliance (J) decreased from approximately 1 × 10–5 to <2 × 10–6 Pa–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…Yu et al [54] indicated that the PA leaching rate at the cathode has been found to be about an order of magnitude higher when the fuel cell operating temperature increased from 160°C to 190°C. Crosslinking or creep resistance improvements of the membrane have been proven to be one of the most effective degradation mitigation strategies, and cells constructed based on such membranes have repeatedly been demonstrated to operate for up to 18000 h with average cell voltage degradation rates as low as 1.8 μV h -1 , as summarized in Figure 2(b) based on durability data reported in the literature [55][56][57][58]. It should be remarked that the cells showing the lowest average degradation rates were operated under mild conditions to suppress different modes of degradation.…”
Section: Phosphoric Acid-doped Polybenzimidazole Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu et al [54] indicated that the PA leaching rate at the cathode has been found to be about an order of magnitude higher when the fuel cell operating temperature increased from 160°C to 190°C. Crosslinking or creep resistance improvements of the membrane have been proven to be one of the most effective degradation mitigation strategies, and cells constructed based on such membranes have repeatedly been demonstrated to operate for up to 18000 h with average cell voltage degradation rates as low as 1.8 μV h -1 , as summarized in Figure 2(b) based on durability data reported in the literature [55][56][57][58]. It should be remarked that the cells showing the lowest average degradation rates were operated under mild conditions to suppress different modes of degradation.…”
Section: Phosphoric Acid-doped Polybenzimidazole Membranesmentioning
confidence: 99%
“…The underlying reason for the improved stability of the crosslinked and creep-resistant membranes remains to be explained. A plausible explanation is that the enhanced [55,56], Pingitore et al [57], and Sondergaard et al [58]. The reader is referred to the cited references for further details about the MEA components and test conditions.…”
Section: Phosphoric Acid-doped Polybenzimidazole Membranesmentioning
confidence: 99%
“…And aside from the acid leakage of membranes, the control of the polyphosphoric acid content is also critical in PBI membranes in which effective catalyst areas can sharply decline due to the adsorption of concentrated phosphoric acid [142]. Furthermore, Pingitore et al [143] synthesized a poly(2,2ʹ-(1,4-phenylene)5,5ʹ-bibenzimidazole) meta/para-PBI random copolymer through a poly (phosphoric acid) process in which the compressive creep compliance was less than 2 × 10 −6 Pa −1 and reported that this membrane exhibited a high proton conductivity of 150 mS cm −1 at typical operating temperatures of 160-200 °C and an exceptionally lowvoltage decay of 0.67 μV h −1 at 160 °C for more than 2 years.…”
Section: Ion-solvating Polymersmentioning
confidence: 99%
“…Most ECHP studies that operate above 100 1C examine different types of PBI chemistries. [30][31][32][33]37,38 These studies often use commercially available electrodes (e.g., BASF electrodes) and little attention has been given to how the electrode binder impacts ECHP performance. New materials for fuel cells, ECHPs, and water electrolyzers are characterized in ex situ experimental setups for assessing their likelihood to improve the electrochemical cell performance.…”
Section: Introductionmentioning
confidence: 99%